Special Topics in Structural Dynamics, Volume 6 Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics 2017 - Dervilis, Nikolaos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Special Topics in Structural Dynamics, Volume 6: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the sixth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Experimental Methods Analytical Methods General Dynamics & Modal Analysis General Dynamics & System Identification Damage Detection .
Chapter 1.Harmonic Forcing of a Two-Segment Euler-Bernoulli Beam -- Chapter 2.A new Surrogate Modeling Method Associating Generalized Polynomial Chaos Expansion and Kriging for Mechanical Systems Subjected to Friction-induced Vibration -- Chapter 3. Multi-Objective Parametric Optimization of an Equilibrator Mechanism -- Chapter 4. Development of a Numerical Model for Dynamic Analysis of a Built-up Structure by a Two-Step FEM-Test Correlation Approach -- Chapter 5. Testing Methods for Verification of a Mounted Accelerometer Frequency Response -- Chapter 6. Experimental Evaluation and Statistical analysis of Synchronous Averaging -- Chapter 7. Optimization of a Zigzag Shaped Energy Harvester for Wireless Sensing Applications -- Chapter 8. Fuzzy Finite Element Model Updating Using Metaheuristic Optimization Algorithms -- chapter 9. The Combination of Testing and 1D Modelling for Booming Noise Prediction in the Model Based System Testing Framework -- Chapter 10. Structural Coupling Analyses ofExperimental Models in a Virtual Shaker Testing Environment for Numerical Prediction of a Spacecraft Vibration Test -- Chapter 11. Establishment of Full-field, Full-order Dynamic Model of Cable Vibration by Video Motion Manipulations -- Chapter 12. Analyses of Target Definition Processes for MIMO Random Vibration Control Tests -- Chapter 13. Material Characterization of Self-Sensing 3D Printed Parts -- Chapter 14. Trajectory Tracking and Active Vibration Suppression on a Flexible Tower Crane -- Chapter 15.On a Grey Box Modelling Framework for Nonlinear System Identification -- Chapter 16. In-Process Monitoring of Automated Carbon Fibre Tape Layup using Ultrasonic Guided Waves -- Chapter 17.Development of a Mathematical Model to Design the Control Strategy of a Full Scale Roller-rig.
Keywords: Mechanics, Applied; Solids; Multibody systems; Vibration; Mechanical engineering; Civil engineering; Solid Mechanics; Multibody Systems and Mechanical Vibrations; Mechanical Engineering; Civil Engineering